EFFECT OF THE UNCERTAIN ANGULAR MISALIGNMENT ON FATIGUE LIFE OF ANGULAR CONTACT BALL BEARINGS OF SPINDLE SYSTEM - ZHANG MengQi; DU DongXu; XIE LiYang; ZHANG Yu (Jixie qiangdu)
The effect of angle misalignment of bearing on bearing fatigue life in spindle system with non-ideal installation conditions was studied in this paper. For achieving this,firstly,the analysis model of multiple bearings-spindle system was introduced. The solution method for multi-degree-of-freedom system model was proposed,and the validity of the model was verified. In addition,taking the four bearings-spindle system as the research object,the uncertain angular misalignment was considered and the angular misalignment was assumed to be normal distribution. Based on the system model,the contact force distribution of balls of bearing was analyzed under different spindle speeds and angular misalignment. Finally,the fatigue life of each bearing was calculated by the life theory. The results show that the uncertain angular misalignment can lead to significant dispersion of bearing life. For the preloaded bearing of system,the fatigue life without angular misalignment is the upper limit of that with angular misalignment. With the decrease of spindle speed,the bearing life without angular misalignment is significantly greater than the minimum bearing life with angular misalignment.